Effectiveness of RFDT learning based on TPACK framework in improving the critical and creative thinking abilities of prospective biology teacher students - Bea Hana Siswati; Slamet Hariyadi (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2024)
The emphasis on 21st-century skills, particularly critical and creative thinking, has driven educational advancements, including technology integration through frameworks like TPACK (Technological Pedagogical Content Knowledge). This study examines the effectiveness of RFDT (Reading, Finding, Discussing, and Talking) learning grounded in TPACK to enhance students' critical and creative thinking. Using a one-group pretest-posttest pre-experimental design, 30 biology education students in professional education courses were assessed through critical and creative thinking essay tests administered before and after TPACK-based RFDT learning. Findings reveal a significant improvement in both critical thinking scores (from 62.3 to 77.63) and creative thinking scores (from 61.8 to 80.76), with p < 0.05. These results highlight the potential of TPACK-based RFDT in developing essential thinking skills, promoting a dynamic and interactive learning environment. Future research with a larger sample and advanced experimental designs is recommended to validate these findings further.Abstrak. Penekanan pada keterampilan abad ke-21, terutama berpikir kritis dan kreatif, telah mendorong kemajuan pendidikan, termasuk integrasi teknologi melalui kerangka TPACK (Technological Pedagogical Content Knowledge). Studi ini meneliti efektivitas pembelajaran RFDT (Reading, Finding, Discussing, and Talking) berbasis TPACK dalam meningkatkan kemampuan berpikir kritis dan kreatif siswa. Dengan menggunakan desain pra-eksperimen pretest-posttest satu kelompok, 30 mahasiswa program studi pendidikan biologi yang mengikuti mata kuliah profesi kpendidikan  dinilai melalui tes esai berpikir kritis dan kreatif yang diberikan sebelum dan sesudah pembelajaran RFDT berbasis TPACK. Hasilnya menunjukkan peningkatan signifikan pada skor berpikir kritis (dari 62,3 menjadi 77,63) dan skor berpikir kreatif (dari 61,8 menjadi 80,76), dengan p < 0,05. Hasil ini menunjukkan potensi RFDT berbasis TPACK dalam mengembangkan keterampilan berpikir yang esensial, serta mendorong lingkungan belajar yang dinamis dan interaktif. Penelitian selanjutnya dengan sampel yang lebih besar dan desain eksperimental yang lebih kompleks direkomendasikan untuk memperkuat temuan ini.